Karyotype variability in neotropical catfishes of the family Pimelodidae (Teleostei: Siluriformes) - Américo Moraes Neto; Maelin da Silva; Daniele Aparecida Matoso; Marcelo Ricardo Vicari; Mara Cristina de Almeida; Maria João Collares-Pereira; Roberto Ferreira Artoni (Neotropical Ichthyology, 2011)
Karyotypic data are presented for four species of fish belonging to the Pimelodidae family. These species show a conserved diploid number, 2n = 56 chromosomes, with different karyotypic formulae. The analyzed species showed little amount of heterochromatin located preferentially in the centromeric and telomeric regions of some chromosomes. The nucleolus organizer regions activity (Ag-NORs) and the chromosomal location of ribosomal genes by fluorescent in situ hybridization (FISH), with 18S and 5S probes, showing only one chromosome pair marked bearer of ribosomal genes, the only exception was Pimelodus britskii that presented multiple NORs and syntenic location of the 18S and 5S probes. Non-Robertsonian events, as pericentric inversion and NORs duplication are requested to explain the karyotype diversification in Pseudoplatystoma from the rio Paraguay (MS), Pimelodus from the rio Iguaçu (PR), Sorubim from the rio Paraguay (MS) and Steindachneridion from the rio Paraíba do Sul (SP). The obtained data for the karyotype macrostructure of these species corroborates a conserved pattern observed in Pimelodidae. On the other hand, interspecific variations detected by molecular cytogenetics markers made possible cytotaxonomic inferences and differentiation of the species here analyzed. Dados cariotípicos são apresentados para quatro espécies da família Pimelodidae. Todas apresentaram o mesmo número diploide, 2n = 56 cromossomos, com diferenças nas fórmulas cariotípicas. As espécies aqui analisadas mostraram pouca quantidade de heterocromatina localizada preferencialmente na região centromérica e telomérica de alguns cromossosmos do complemento cariotípico. As regiões organizadoras de nucléolo (Ag-RONs) e a localização dos genes ribossomais pela hibridização in situ fluorescente (FISH), com sondas 18S e 5S, evidenciaram somente um par cromossômico marcado portador de genes ribossomais, à exceção de Pimelodus britskii que apresentou NORs múltiplas e localização sintênica das sondas 18S e 5S. Eventos não-Robertsonianos, como inversão pericêntrica e duplicação das NORs são requeridos para explicar a diversificação cariotípica em Pseudoplatystoma do rio Paraguai (MS), Pimelodus do rio Iguaçu (PR), Sorubim do rio Paraguai (MS) e Steindachneridion do rio Paraíba do Sul (SP). Os dados obtidos para a macroestrutura cariotípica destas espécies corrobora um padrão conservado observado na família Pimelodidae. Por outro lado, evidências de variações interespecíficas pelos marcadores de citogenética molecular empregados possibilitam inferências citotaxonômicas e diferenciação das espécies aqui analisadas.